Multiagent Consensus Control under Network-Induced Constraints - Won Il Kim; Rong Xiong; Qiuguo Zhu; Jun Wu (Journal of Applied Mathematics)
Mean consensus problem is studied using a class of discrete time multiagent systems in which information exchange is subjected to some network-induced constraints. These constraints include package dropout, time delay, and package disorder. Using Markov jump system method, the necessary and sufficient condition of mean square consensus is obtained and a design procedure is presented such that multiagent systems reach mean square consensus.